The Use of Spot Image for Mangrove Inventory in Cimanuk Delta West Java, Indonesia - Hartono . (Faculty of Geography, Universitas Gadjah Mada, 1994)
This study deals with an application of SPOT satellite data for mangrove forest inventory in Cimauuk Delta West Java (Indonesia). Mangrove of the area (7100 Ha) has been gradually decreasing by human pressure especially for fisheries purposes. In fact, mangrove here is a result of afforestation since1960, with Rhizophora mucronata and R. apiculata as main planted species. Other species are Lunmitzera racemosa, Excoecaria agallocha, Bruguiera gymnorhiza and Avicennia which grow naturally. SPOT data were digitally analysed using Didactim software. A color composite image was analysed. A barycentric supervised classification and textural analysis were applie.d. As an intermediate data, infrared color aerial photographs at 1130,000 (1981) were interpreted manually.At least two mangrove types of mangrove could be identified from the SPOT image. Dense mangrove was found in Petak 7, Petak 8, Petak 9 and Petak 12. In the other Petaks, mangrove were less than 20% of their surface. Mangrove of Rhizophora in 26 Petaks covered 290 Ha only.